War, guilt, and world politics after world war II - Berger, Thomas U (Cambridge Cambridge University Press, 2012)
"This book describes how the states in post-1945 Austria, Germany, and Japan have tried to deal with the legacy of the Second World War and how their policies have affected their relations with other countries in the region"--
"We live in an age of apology and recrimination. Over the past two decades, the world has witnessed an unprecedented outpouring of expressions of contrition by political leaders for past injustices their countries are held responsible for. At the same time, there has been an upsurge in demands for apologies, restitution and variety of forms of compensation on the behalf of groups and nations that feel they have been victimized. The Federal Republic of Germany may well be the paradigmatic example of this trend. More than sixty years after the end of World War II it continues to wrestle with the legacies of the Third Reich, offering long-overdue compensation to the hundreds of thousands of former slave laborers while arguing with the governments of Poland and the Czech Republic over how to commemorate the millions of ethnic Germans who were driven out of Eastern Europe in the aftermath of the war. Germany might seem to have long been a special case in this regard, burdened as it is by an especially terrible history. Yet other examples abound: the bitter disputes between Russia and its neighbors over how to view the Soviet Union, the disagreement between Israelis and Palestinians over whether the Arab population in Israel had fled or were driven from their homes in 1947, or repeated accusations in Asia that Japan has failed to apologize adequately for its history of atrocity and aggression before 1945. And the list could well be extended almost ad infinitum"--
Machine generated contents note: 1. Politics and memory in an age of apology; 2. Germany: the model penitent; 3. Austria: the prodigal penitent; 4. Japan: the model impenitent?; 5. Asia: the geopolitics of remembering and forgetting: towards an expanded model; 6. Conclusions: the varieties of penitence.
Includes bibliographical references and index.
Keywords: World War, 1939-1945 -- Reparations; World War, 1939-1945 -- Historiography; Restitution -- Europe; Reparations for historical injustices -- Europe; Cultural property -- Repatriation -- Europe; World War, 1939-1945 -- Confiscations and contributions -- Europe; Guilt -- Political aspects; World War, 1939-1945 -- Psychological aspects; War victims; Political Science / General